2017
DOI: 10.1111/tpj.13434
|View full text |Cite
|
Sign up to set email alerts
|

The cotton β‐galactosyltransferase 1 (GalT1) that galactosylates arabinogalactan proteins participates in controlling fiber development

Abstract: Arabinogalactan proteins (AGPs) are highly glycosylated proteins that play pivotal roles in diverse developmental processes in plants. Type-II AG glycans, mostly O-linked to the hydroxyproline residues of the protein backbone, account for up to 95% w/w of the AGP, but their functions are still largely unclear. Cotton fibers are extremely elongated single-cell trichomes on the seed epidermis; however, little is known of the molecular basis governing the regulation of fiber cell development. Here, we characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 53 publications
0
37
0
Order By: Relevance
“…The surface of mature fibers was examined by cold‐field scanning electron microscopy (Hitachi) after dehydration and platinum spraying. Additionally, resin‐embedded cross‐sections of 30 DPA fibers were observed and photographed under a light microscope as described previously (Qin et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The surface of mature fibers was examined by cold‐field scanning electron microscopy (Hitachi) after dehydration and platinum spraying. Additionally, resin‐embedded cross‐sections of 30 DPA fibers were observed and photographed under a light microscope as described previously (Qin et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…F); this gene encodes a galactosyltransferase for arabinogalactan protein galactosylation during backbone formation (Henrissat et al ). A novel GT31 gene, GhGalT1 , participates in the regulation of cell wall pectin biosynthesis during plant development (Qin et al ) and the control of fibre development (Qin et al ) in cotton. In plants, the GT43 family is a large CAZyme family, and 10 candidate genes were identified in the N. affinis transcriptome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In tobacco, it was reported that the sense or antisense expression of sequences encoding O-methyltransferase (OMT) could regulate enzyme activity of lignin synthesis [51]. The ber length of transgenic cotton overexpressing GhGalT1 was shorter than that of wild type, while in GhGalT1 silenced line, the ber length was signi cantly increased than that of wild type [52].…”
Section: Discussionmentioning
confidence: 99%